Beginning React: Simplify Your Frontend Development Workflow and Enhance the User Experience of Your Applications with React - Chiarelli, Andrea (Packt Publishing, Limited, 2018)
Projects like Angular and React are rapidly changing how development teams build and deploy web applications to production. In this book, you'll learn the basics you need to get up and running with React and tackle real-world projects and challenges. It includes helpful guidance on how to consider key user requirements within the development.